Placenta is Capable of Protecting the Male Fetus from Exposure to Environmental Bisphenol A - Lukasiewicz Monika; Czerniecki Jan; Ponikwicka-Tyszko Donata; Sztachelska Maria; Hryniewicka Marta; Nalewajko-Sieliwoniuk Edyta; Wiczkowski Wieslaw; Banaszewska Beata; Milewski Robert; Toppari Jorma; Huhtaniemi Ilpo; Rahman Nafis A.; et al. (SPRINGER, 2022)
Embryo-fetal exposure to bisphenol A (BPA) could be related to poor male reproductive parameters in rodents, but this concept has not been convincingly confirmed in humans. We investigated the association of environmental BPA exposure of pregnant women with selected endocrine and anthropometric parameters of male newborns. We analyzed plasma BPA from pregnant mothers, umbilical cord, and placental tissues (n = 117/each group) by liquid chromatography and mass spectrometry. LH, FSH, AMH, TGF beta 2, inhibin B, and selected sex steroids were measured in cord plasma. The infant anthropometric parameters included anogenital distance, stretched penile length, head circumference, birthweight, and length. The median BPA concentrations in maternal and umbilical cord plasma, and in placental tissue were 19.0, 8.0, and 22.2 nmol/L, respectively, the levels thus being over twofold lower in the fetal circulation than in the mother or placenta. The BPA concentrations measured were 100-1000-fold lower than those demonstrated in animal experiments to have endocrine disrupting effects. Multivariable regression analysis indicated no significant correlations between the maternal/fetal/placental BPA concentrations and any of the hormone levels or anthropometric parameter measured. Plasma concentrations of BPA confirmed both maternal, placenta, and fetal exposure to environmental BPA, but the concentrations were orders of magnitude lower than those with documented endocrine disrupting activity. Moreover, the maternal/fetal concentration gradient as well as the lack of correlations of BPA levels with any major endocrine or anthropometric parameters measured in the newborns suggest a protective role for the placenta in reducing fetal exposure to the environmental BPA.